1060. Duration of Seroprevalence among Individuals Previously Infected with SARS-CoV-2 and their Household Contacts. (15th December 2022) - Altamirano, Jonathan; Lopez, Marcela; Lopez, Marcela; Chun, Leanne X; Tam, Grace K; Robinson, India; Shaikh, Nuzhat; Leary, Sean; Stainton, Emma; Robinson, Makeda L; Behl, Rasika; Thiessen, Rosita; et al.
Abstract: Background: Serological tests directed against SARS-CoV-2 can provide information about the timing of infection and immunity against the virus. However, the kinetics of the host immune response to SARS-CoV-2 remain poorly understood. We established a household transmission study to analyze the serological responses within households, to determine longitudinal immune responses to infection. Methods: From April 2020 to April 2022, we prospectively enrolled 76 households with at least one RT-PCR confirmed case of COVID-19. Participants were asked to provide blood samples at three time points: at baseline within 2 weeks of the index's diagnosis of COVID-19, and at one- and three-months post-enrollment. Samples were tested for the presence of IgG antibodies against SARS-CoV-2 spike protein via an FDA EUA approved ELISA. Demographics, medical history, and symptomatology were also collected. Results: To date, we have analyzed 238 serologic samples from 135 participants, including 82 baseline samples, 89 one-month samples, and 67 three-month samples. At baseline, 67.8% (n=40/59) of all confirmed cases tested positive for SARS-CoV-2 antibodies, which increased to 86.4% (n=57/66) at the one month, and 85.1% at three months (n=40/47). Of those confirmed infected participants that failed to seroconvert at baseline, almost all reported symptoms (n=14/19, 73.7%) and did not have chronic medical conditions (n=17/19, 89.5%). Of the 19, 3 failed to seroconvert by their third visit. All individuals who were fully vaccinated at the time of each visit tested positive for antibodies at baseline (n=26), one-month (n=27), and three-months (n=20). Of those who were not fully vaccinated, 56 (41.1%) were positive for antibodies at baseline, 62 (59.7%) were positive at one -month, and 47 (63.8%) at three-months. Differences in seropositivity rates between pediatric and adult participants, as well as between index cases and household contacts, at each visit were also identified (Table 1). Conclusion: Identifying differences in seroprevalence in various demographic groups can provide insight into longitudinal immune responses post-infection. Future analyses on seropositivity among previously infected individuals who received therapeutics may be of interest. Disclosures: Andra L. Blomkalns, MD, MBA, Eli Lilly and Company: Grant/Research Support Yvonne A. Maldonado, MD, Pfizer: Grant/Research Support|Pfizer: Member, DSMB, Pfizer Meningococcal Vaccine clinical trial.